QR Code-Based Information System Designed to Display Irrigation Unit Data - Elisabet Yunaeti Anggraeni; Sri Hartati; Dedi Murwanto (bit-Tech, 2025)
The management and maintenance of irrigation unit data are still conducted manually, leading to inefficiencies in record-keeping, data retrieval, and asset monitoring. The absence of a structured digital system makes it difficult to track the location, specifications, history, and condition of irrigation units, which affects operational efficiency. To address this issue, a QR Code-based information system was developed to provide quick and accurate access to irrigation unit data. This system was developed using the System Development Life Cycle (SDLC) methodology with the Waterfall model, ensuring a structured and systematic approach in each development phase, including analysis, design, implementation, testing, and maintenance. Various software tools such as Sublime Text 3, XAMPP Control Panel v3.2.2, and Google Chrome were used to support system development, while QR Code scanning was integrated through mobile devices for ease of access. The system was tested using the black box method to evaluate its functionality and performance. The results showed that the system effectively displays irrigation unit information through QR Code scanning. The maximum readable QR Code size is 10 cm² with an optimal scanning distance of up to 50 cm. The system functions reliably under various lighting conditions, except when the QR Code is significantly folded or scratched, which affects readability. This research demonstrates that a QR Code-based information system can improve efficiency in irrigation unit management by providing real-time, accessible, and structured data. Future enhancements may include additional features such as location mapping and automated reporting for maintenance and issue tracking.